A feasibility study of using composite reinforcement in transport and power industry structures. Issue 3 (3rd July 2017) - Vanagas, Egidijus; Kliukas, Romualdas; Lukoševičienė, Ona; Maruschak, Pavlo; Patapavičius, Andrius; Juozapaitis, Algirdas
Abstract: About 92% of Lithuanian bridges are made of reinforced concrete. Therefore, the problem of increasing the reliability and service life of their structures is most important for ensuring effective operation of transport buildings. The main factor causing transport building structures' failure is associated with high water permeability and low resistance to attack by corrosive media of concrete used in construction. Ports, bridges, tunnels, viaducts make a group of transport structures strongly attacked by the aggressive media, e.g. cold air, water, ice, salts, etc. Though the members of these structures (e.g. columns, beams) are usually designed for 50 years of service, they often require a major overhaul or strengthening, when less than the half of this period has passed. Most of the damaged structures are the destroyed protective concrete layer and the corroded steel reinforcement. The corrosion of steel reinforcement is the main problem, causing the decrease of strength in the structures' and their brittle failure. Now, composite reinforcement is the alternative material used for reinforcing in the considered structures. Its mechanical properties, including the tensile strength and resistance to the attack of aggressive media, are similar to or even better than those of commonly used steel reinforcement. The experimental data on using composite reinforcement in the compression members or in the compressed zones of flexural members of the structures are lacking. Therefore, most of design codes do not mention or even do not recommend using composite reinforcement in these cases. The paper presents the analysis of the possibilities of using composite reinforcement in transport and power industry structures. This article has been corrected since first published. Please see the statement of correction (DOI:10.3846/16484142.2017.1358932 of the erratum).